2012
DOI: 10.1016/j.actatropica.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in selected non-Amazonian countries of Latin America

Abstract: Approximately 170 million inhabitants of the American continent live at risk of malaria transmission. Although the continent’s contribution to the global malaria burden is small, at least 1 to 1.2 million malaria cases are reported annually. Sixty per cent of the malaria cases occur in Brazil and the other 40% are distributed in 20 other countries of Central and South America. Plasmodium vivax is the predominant species (74.2 %) followed by P. falciparum (25.7 %) and P. malariae (0.1%), and no less than 10 Ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 120 publications
(150 reference statements)
0
91
0
4
Order By: Relevance
“…In this series, although the frequency was low, the number of mixed malaria cases (due to P. vivax and P. falciparum, 5.4%) was quite high compared to other studies in Latin America, which usually have reported less than 2% [7,[26][27][28]. However, the mixed malaria cases were those that most frequently presented complications and required the patient to be hospitalized in this study (crude OR = 5.535; 95%CI 1.81-16.9).…”
Section: Discussionmentioning
confidence: 48%
“…In this series, although the frequency was low, the number of mixed malaria cases (due to P. vivax and P. falciparum, 5.4%) was quite high compared to other studies in Latin America, which usually have reported less than 2% [7,[26][27][28]. However, the mixed malaria cases were those that most frequently presented complications and required the patient to be hospitalized in this study (crude OR = 5.535; 95%CI 1.81-16.9).…”
Section: Discussionmentioning
confidence: 48%
“…Three malaria-endemic settings with different transmission patterns were selected: Tierralta (Department of Có rdoba) in the northern region of Colombia, Quibdó (Department of Chocó ) in the western region, and Tumaco (Department of Nariñ o) in the southwest region along the Pacific coast. Both P. vivax and P. falciparum are transmitted in these regions in different proportions, with an unstable endemic pattern 8,12 ( Figure 1). Tierralta has a population of approximately 90,000 inhabitants, with most inhabitants characterized as mestizos and an indigenous minority (Emberá Katío); the predominant malaria parasite species in this region is P. vivax (83%).…”
Section: Methodsmentioning
confidence: 99%
“…2,[4][5][6][7] The human population in this region has a different genetic background, P. vivax is the most prevalent malaria parasite species, malaria transmission intensity is low and unstable, and the young adult population seems to be at higher risk for malarial anemia than children. 8,9 As a consequence of this complexity, malaria and anemia exhibit epidemiological characteristics that seem to be unique to the region and remain poorly understood. In 2012, approximately 469,000 malaria cases (microscopically confirmed) were reported on the South American continent, mainly caused by P. vivax (approximately 74%) and P. falciparum (approximately 26%).…”
Section: Introductionmentioning
confidence: 99%
“…6 There have been few clinical studies that investigated the effects of malaria in pregnant women in malaria-endemic regions of Latin America, where infections by Plasmodium vivax are more prevalent. 7 A search performed in the electronic databases PUBMED, MEDLINE, and BIREME in October of 2012, using the MeSH terms malaria, pregnancy, clinical findings, and Latin America, resulted in four publications on the subject. [8][9][10][11] To characterize the clinical and laboratory findings of malaria in pregnancy (MIP) in a non-Amazonian endemic region of Colombia, we enrolled pregnant women who had been diagnosed with infection by Plasmodium spp.…”
Section: Introductionmentioning
confidence: 99%